Contralateral Inhibition of Click- and Chirp-Evoked Human Compound Action Potentials - Smith, Spencer B.; Lichtenhan, Jeffery T.; Cone, Barbara K. (Frontiers in Neuroscience, 2017)
Cochlear outer hair cells receive direct efferent feedback from the caudal auditory brainstem via the medial olivocochlear (MOC) bundle. This circuit provides the neural substrate for the MOC reflex, which inhibits cochlear amplifier gain and is believed to play a role in listening in noise and protection from acoustic overexposure. The human MOC reflex has been studied extensively using otoacoustic emissions (OAE) paradigms; however, these measurements are insensitive to subsequent “downstream” efferent effects on the neural ensembles that mediate hearing. In this experiment, click- and chirp-evoked auditory nerve compound action potential (CAP) amplitudes were measured electrocochleographically from the human eardrum without and with MOC reflex activation elicited by contralateral broadband noise. We hypothesized that the chirp would be a more optimal stimulus for measuring neural MOC effects because it synchronizes excitation along the entire length of the basilar membrane and thus evokes a more robust CAP than a click at low to moderate stimulus levels. Chirps produced larger CAPs than clicks at all stimulus intensities (50-80 dB ppeSPL). MOC reflex inhibition of CAPs was larger for chirps than clicks at low stimulus levels when quantified both in terms of amplitude reduction and effective attenuation. Effective attenuation was larger for chirp- and click-evoked CAPs than for click-evoked OAEs measured from the same subjects. Our results suggest that the chirp is an optimal stimulus for evoking CAPs at low stimulus intensities and for assessing MOC reflex effects on the auditory nerve. Further, our work supports previous findings that MOC reflex effects at the level of the auditory nerve are underestimated by measures of OAE inhibition.